Probing structural chirality with high‐energy synchrotron radiation. Issue 3 (16th May 2016) - Dyadkin, Vadim; Wright, Jon; Pattison, Philip; Chernyshov, Dmitry
Abstract : In spite of the low absolute values of the resonant contribution at high energy, accurate measurements of the Bragg intensities up to highQ values are capable of providing data sufficient for absolute structure determination. Abstract : The absolute structure has been determined for MnSi with data collected using synchrotron radiation with E = 78.3 keV (0.158 Å). At this energy, the resonant scattering contribution from MnSi is very small ( f ′Mn = −0.0397, f ′′Mn = 0.0385, f ′Si = −0.0197, f ′′Si = 0.0027), but the large number of observed Bijvoet differences together with a wideQ range make absolute structure determination possible. A comparison with the data collected at E = 18 keV (0.68 Å) ( f ′Mn = 0.2858, f ′′Mn = 0.6739, f ′Si = 0.0653, f ′′Si = 0.0646) for the same crystal shows the correctness of the absolute structure measured at the higher energy. A similar data collection has also been done at E = 65.3 keV (0.19 Å) for a single crystal of Fe0.7 Co0.3 Si with known absolute structure. In all cases, the absolute structure was correctly determined by analysing the statistical distribution of the chirality measure. Statistical descriptors of the refinements, the Flack parameter and the distribution of Parsons quotients are discussed for all presented experiments.